Answer:
<h2>d(4) = 64</h2>
Step-by-step explanation:
d(1) = 13
d(n) = d(n - 1) + 17
where
n is the nth term
To find the 4th term we must first find the second term use it to find the 3rd term and use the 3rd term to find the 4th term
So we have
<u>For the 2nd term</u>
That's d(2)
We have
d(2) = d(2-1) + 17
d(2) = d(1) + 17
But d(1) = 13
d(2) = 13 + 17 = 30
<u>For the 3rd term d(3)</u>
That's
d(3) = d(3 - 1) + 17
d(3) = d(2) + 17
d(3) = 30 + 17 = 47
<u>For the 4th term that's d(4)</u>
We have
d(4) = d(4 - 1) + 17
d(4) = d(3) + 17
d(4) = 47 + 17
We have the final answer as
<h3>d(4) = 64</h3>
Hope this helps you
Answer:
FG = 47
Step-by-step explanation:
The opposite sides of a parallelogram are parallel and congruent, thus
EH = FG, that is
5z - 18 = 3z + 8 ( subtract 3z from both sides )
2z - 18 = 8 ( add 18 to both sides )
2z = 26 ( divide both sides by 2 )
z = 13
Hence
FG = 3z + 8 = (3 × 13) + 8 = 39 + 8 = 47
I dont remember that one sorry
Step-by-step explanation: